Utilization of Avocado and Mango Fruit Wastes in Multi-Nutrient Blocks for Goats Feeding: In Vitro Evaluation - Carlos Navarro Marcos; María Dolores Carro; Julia E. Fernández-Yepes; Lesly Arbesu; Eduarda Molina-Alcaide (Animals, 2020)
This study was conducted to investigate the nutritive value of avocado and mango fruit wastes, and to assess the possibility of preserving the wastes into multi-nutrient blocks (MB). Both peels and a pulp:peels (PP) mixture of each fruit were analyzed for chemical composition and in vitro fermentation with goats’ ruminal fluid. Wastes had low-dry matter (DM) content (<250 g/kg), with those from mango having high non-structural carbohydrates content (>800 g/kg DM) and those from avocado high fat levels (>580 g/kg DM). Mango wastes were fermented at a greater extent and faster rate than avocado ones. The PP mixture of each fruit was included into multi-nutrient blocks (MB) formulated to have similar chemical composition. There were only subtle differences in the fermentation of MB including wastes from either avocado or mango, but fermentation of avocado-MB resulted in significantly (p ≤ 0.032) greater acetate and lower propionate proportions than mango-MB. Including the PP mixture in the formulation of MB for goats feeding is a feasible option to reduce the environmental impact of avocado and mango fruit wastes, but studies on the acceptance of the MB by goats and their stability over long-time storage periods are needed.